Analysis of Medical Equipment Maintenance Management Elements at Brawijaya Level III Hospital, Surabaya - Fitriardi, Sandhi; Andriyanto, Ronny; Sri Mulawardhani, Dyna; -, Chamariyah (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
This study examines the management of medical equipment maintenance at Brawijaya Level III Hospital, Surabaya. The study highlights challenges such as limited human resources, budget constraints, and inadequate training for staff responsible for maintaining medical equipment. Although Standard Operating Procedures (SOPs) for maintenance exist, their implementation is suboptimal and requires regular updates. While the hospital's infrastructure is generally adequate, the need for additional equipment, particularly for digital-based medical devices, is notable. This study suggests that implementing a Computerized Maintenance Management System (CMMS) can improve the efficiency of preventive and corrective maintenance processes. Furthermore, improving staff competency through training is crucial to ensuring smooth operational maintenance. Effective maintenance not only improves service quality but also enhances patient safety in hospitals. This study recommends increasing the number of biomedical engineering specialists, regular updates to the maintenance system, and more flexible and responsive budget allocation to ensure sustainable medical facility maintenance.